2021
DOI: 10.1007/s00268-021-05993-w
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Medullary Thyroid Carcinoma: Genotype, Phenotype and Outcomes in a North Indian Cohort

Abstract: Background Aggressiveness of hereditary medullary thyroid carcinoma (hMTC) has been conventionally described to correlate with American Thyroid Association (ATA) risk groups based on RET mutations. Recent evidence increasingly contradicts this notion. We studied the RET genotype and its correlation with disease phenotype and survival outcomes in a cohort of hMTC patients. Methods In a retrospective cohort of 55 hMTC patients from 23 families treated at a north Indian tertiary care institute over 15‐years, RET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, some scholars point out that this classification method cannot fully reflect the biological behavior of MTC [33]. Studies have shown that ATA guidelines for the classification of RET mutation risk are insufficient to accurately predict biochemical and clinical cure rates, especially in high-risk and intermediate-risk groups [34]. And overall survival after MTC diagnosis and progression to metastasis are similar in patients with high-risk and moderate-risk RET mutations.…”
Section: The Risk Level Of Ret Mutations Involved In Fmtcmentioning
confidence: 99%
“…However, some scholars point out that this classification method cannot fully reflect the biological behavior of MTC [33]. Studies have shown that ATA guidelines for the classification of RET mutation risk are insufficient to accurately predict biochemical and clinical cure rates, especially in high-risk and intermediate-risk groups [34]. And overall survival after MTC diagnosis and progression to metastasis are similar in patients with high-risk and moderate-risk RET mutations.…”
Section: The Risk Level Of Ret Mutations Involved In Fmtcmentioning
confidence: 99%
“…Once MTC has developed, cure rate and survival rates seem to depend on the disease stage rather than the pathogenic variant. 26 …”
Section: Medullary Thyroid Carcinomamentioning
confidence: 99%